Penggunaan Media pada Pembelajaran Daring Tema 7 “Peristiwa dalam Kehidupan” Kelas V di SDN Sumbersari 1 Malang - Sukamti Sukamti; Mar’atus Sholichah; Sri Estu Winahyu; Mar’atus Sholichah; Sri Estu Winahyu (Universitas Negeri Malang, 2021)
Abstract: Learning media is one of the important components in learning. Before using the media the teacher must pay attention to the planning and criteria for selecting a good media. So that the desired learning objectives can be achieved optimally. However, not all teachers plan, select, and use learning media properly and appropriately. This study aims to describe the planning, selection, and use of media as well as the obstacles experienced in implementing the use of media in online learning Theme 7